Checklist and distribution of Euphorinae (Hymenoptera: Braconidae) from Türkiye - Beyarslan, Ahmet; Erdoğan, Özlem Çeti̇n (Zootaxa, 2026)
The Euphorinae (Hymenoptera: Braconidae) species recorded from Türkiye are listed, the present total number being 85. Changes with respect to the Turkish fauna are briefly annotated and the distributions for all species in each of the 75 provinces (except for Hakkari, İstanbul, Kocaeli, Şırnak and Uşak provinces ) are presented. Of these, 46 species are distributed only in Asian Türkiye and 4 species are distributed only in European Türkiye, while 35 species occur in both. The checklist includes synonyms, zoogeographical region(s), hosts, host plants of host species, and parasitoid data for the species. The number of species within each tribe found in Türkiye is represented by: Centistini Capek=7, Dinocampini Shaw=2, Euphorini Foerster=9, Helorimorphini Schmiedeknecht=4, Meteorini Cresson=33, Neoneurini Bengtsson=4, Perilitini Foerster=16, Pygostolini Belokobylskij=3, Syntretini Shaw=3, and Townesilitini Shaw=4.